Vpliv oktobrske revolucije na družino barona Johanna von Maasburga, avstro-ogrskega generalmajorja v pokoju iz Vipave - Miladinović Zalaznik, Mira (Studia Historica Slovenica, 2018)
The Austro-Hungarian Major General Johann von Maasburg (1847-1923) spent the last twenty years of his life in Vipava. The paper, based on his diary preserved in manuscript, on documents that can be found in diferent archives in Vienna (AT-OeStA/KA, DÖW), Ljubljana (ARS, NŠAL, ZAL), Nova Gorica (PANG) and Munich (the Maasburg Family Archives), as well as on the primary and secondary sources, deals with his life and the life of his descendants until a few decades after World War II. It draws our intention to the fact that events resulting from the Russian October Revolution fatefully marked the intellectual, cultivated and brave family of Barons Maasburg who had lived for centuries in Slovene ethnic territory.
Keywords: Maasburg (rodbina); Maasburg, Johann von; oktobrska revolucija 1917; zgodovina